(untitled) (Asian Journal of Medical and Biological Research, 2019)
To evaluate the visual outcome in patients who have had their cataract surgery in a tertiary hospital of Chittagong district in Bangladesh. This is a clinic-based study of consecutive cataract-operated patients who had age-related cataract with vision less than <6/60 before surgery. A total of 228 patients who visited the hospital and met the eligibility criteria were included in the study. The mean age of the patients was 62.46± 10.14 years and 134 (58.8%) were female. A total of 456 surgeries were performed on 228 patients. The most common procedure was small incision cataract surgery (SICS) with intraocular lens (IOL) implantation, operated in 422(92.5%) eyes. Among cataract-operated eyes, 290 (64%) had presenting vision >6/18 and <6/60 were found in 11 (2.4%) eyes. In most of the cases, visual acuity has improved after best correction as the percentages with the best correction were 402(88%) and 7(1.55%) respectively. Analysis of multiple logistic regression shows that patient’s older age (OR 9.101; 95% CI 3.331, 24.869), gender female (OR 2.374 CI 1.403, 4.017), literacy (OR 1.660; CI 1.009, 2.733) and SICS surgery technique (OR 3.540; CI1.298, 9.659) were significantly associated with poor visual outcome. Overall, this study demonstrates that cataract surgery can restore good visual acuity. However, the visual outcome needs to be improved to meet the WHO standard, and more attention should be directed towards monitoring of outcomes and correction of refractive error after cataract surgery. Asian J. Med. Biol. Res. June 2019, 5(3): 212-218